Prednisone for the treatment of withdrawal headache in patients with medication overuse headache: A randomized, double-blind, placebo-controlled study. (February 2013) - Rabe, Kasja; Pageler, Lutz; Gaul, Charly; Lampl, Christian; Kraya, Torsten; Foerderreuther, Stefanie; Diener, Hans-Christoph; Katsarava, Zaza
Purpose: To investigate the efficacy of prednisone for treatment of withdrawal headache in patients with medication overuse headache (MOH). Patients and methods: In this prospective double-blind, placebo-controlled, parallel designed multicentre trial, 96 consecutive patients with MOH were randomized to withdrawal treatment with either 100 mg prednisone or placebo over 5 days. Patients were enrolled if they met the International Headache Society criteria for MOH and were diagnosed with migraine or episodic tension-type headache as primary headache. Exclusion criteria comprised significant neurological or psychiatric disorders. Withdrawal symptoms, including headache severity and intake of rescue medication, were documented for 14 days after randomization. Results: Patients treated with prednisone did not experience fewer hours of moderate or severe headache than patients receiving placebo. However, patients requested less rescue medication within the first 5 days. Conclusions: During withdrawal in MOH, prednisone reduces rescue medication without decreasing the severity and duration of withdrawal headache.